Is intranasal adrenaline effective for the treatment of anaphylaxis? - Tom Jaconelli; Steven Crane (Emergency Medicine Journal, 2026)
A short cut review of the literature was carried out to examine whether there is evidence for the use of intranasal epinephrine in comparison to intramuscular epinephrine to achieve rapid symptom control in patients presenting with anaphylaxis. 113 papers were found of which 8 were directly relevant to the clinical outcome. Seven studies were case series, six of which were published only as conference abstracts and one was an open-label phase III study. 22 studies were also identified, which assessed the pharmacodynamic and pharmacokinetic properties; these were not analysed. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of the best papers are tabulated. The clinical bottom line is that, to date, there is insufficient evidence to determine whether intranasal epinephrine is as effective as intramuscular epinephrine in anaphylaxis. Intramuscular epinephrine remains the standard of care.